AB0220 Disability and Health-Related Quality of Life of Filipino Patients with Rheumatoid Arthritis. (10th June 2014) - Magbitang, A.-T.; Salido, E.
Abstract : Background: Rheumatoid arthritis is associated with physical disability as the disease progresses. Disability, in turn, exerts a significant impact on general health satisfaction and mortality of the RA patient. High disease activity score (DAS 28), low educational attainment, low income, low BMI and longer disease duration are the proposed factors associated with disability. The Health Assessment Questionnaire Disability Index (HAQ-DI) is the gold standard in assessing functional status in RA. Identifying disability through this simple screening tool may help determine additional points of care for our patients. Objectives: To determine the functional status and health-related quality of life of Filipino patients with rheumatoid arthritis. Methods: We collected data on patient demographics, clinical characteristics, and disability using the Health Assessment Questionnaire Disability Index (HAQ-DI). Analysis: T-test, Chi- square test or Fisher's exact test were used to compare nominal data and determine association between population and disease characteristics and disability, as well as disability and health satisfaction. Results: The study population consists of 101 patients with RA. The majority are females in their 6th decade of life who have current or previous employment. Eighty-three patients (82%) had low level of education. Most patients (58%) have rheumatoid arthritis that is more than 3 years in duration; average duration is 8.79 years. Fifty-seven patients (58%) have active RA disease activity (DAS-28 scores of >3.2) at index consultation. Disability is present in 44% and the average HAQ DI score is 0.95 (SD 0.73). There is difficulty in performing activities in almost all domains, particularly in walking (73.27%), arising (65.35%), and gripping (66.34%). Disability is significantly associated with RA duration >3 years (p=0.04), high disease activity (DAS 28 ≥3.2, p=0.02), and BMI <18 kg/m 2 (p<0.01). Forty-nine percent are not satisfied with their overall health. Dissatisfaction is significantly associated with disability (p<0.001), DAS 28 ≥3.2 (p<0.01) and BMI<18 kg/m 2 (p=0.04). Conclusions: More than 50% of RA patients at the Rheumatology clinic of the Philippine General Hospital have significant disability and greater health dissatisfaction. In particular, there is difficulty in walking, arising, and gripping. The HAQ Disability is a validated tool used in clinical trials that shows promise as an important clinical tool for global assessment of disability. This allows for timely and appropriate titration of treatment to improve care. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4770